PENERAPAN MODEL TAI UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS V-B SD NEGERI 053955 PAYA SALIT - Sempa Arihta (JURNAL HANDAYANI PGSD FIP UNIMED, 2016)
Abstract: Application of Model TAI To Improve Student Learning Activities In Maths Lesson In Class V-B Elementary School 053 955 Paya Salit. The purpose of this study was to determine the increased activity of learning and students' mathematics learning outcomes when implementing cooperative learning model Team Assisted Individualization (TAI) in class V-B Elementary School 053 955 Paya Salit T.P. 2015/2016. The subjects were all students of class V-B Elementary School 053 955 Paya Salit T.P. 2015/2016, totaling 24 people. The results showed that the cooperative learning model Team Assisted Individualization (TAI) to increase the average student activity and student learning outcomes in the first cycle, there were 13 students who completed individually while the class was not finished and the second cycle there are 22 students who completed individually and classes have been completed. Keywords: Model TAI, Activities Learning, Learning Outcomes   Abstrak : Penerapan Model TAI Untuk Meningkatkan Aktivitas Belajar Siswa Pada Mata Pelajaran Matematika Di Kelas V-B SD Negeri 053955 Paya Salit. Tujuan penelitian ini adalah untuk mengetahui peningkatan aktivitas belajar dan hasil belajar matematika siswa saat menerapkan model pembelajaran kooperatif tipe Team Assisted Individualization (TAI)  di kelas V-B SD Negeri 053955 Paya Salit T.P. 2015/2016. Subjek penelitian adalah seluruh siswa kelas V-B SD Negeri 053955 Paya Salit T.P. 2015/2016, berjumlah 24 orang. Hasil penelitian menunjukkan bahwa model pembelajaran kooperatif tipe Team Assisted Individualization (TAI) meningkatkan rata-rata aktivitas belajar siswa dan  hasil belajar siswa pada siklus I terdapat 13  siswa yang tuntas secara individu sedangkan kelas belum tuntas dan  siklus II terdapat 22 siswa yang tuntas secara individu dan kelas sudah tuntas.   Kata Kunci : Model TAI, Aktivitas Belajar, Hasil Belajar